Inclusive leadership and innovative work behavior in Generation Z employees: Mediating role of job crafting - Queen Audrey Nasution; Gustiarti Leila; Ferry Novliadi (Jurnal Fokus Manajemen Bisnis, 2025)
The adaptability of Generation Z to technological advances and an ever-changing work environment has made Generation Z dominant in the global job market, such as in the e-commerce sector. This study aims to analyze the impact of inclusive leadership on innovative work behavior among Generation Z employees, considering the mediating role of job crafting. This study uses a quantitative methodology with path analysis to examine the correlations among the constructs in the research framework. Data were collected through a survey of 376 Generation Z employees working at Shopee International Indonesia Company. Analytical procedures were conducted using Smart PLS version 4 to facilitate a comprehensive evaluation of direct and indirect relationships within the research model. The results indicate that inclusive leadership has a positive impact on innovative work behavior and job crafting. Additionally, job crafting not only contributes positively to innovative work behavior but also acts as a mediating variable in the relationship between inclusive leadership and innovative work behavior. This study expands existing understanding of inclusive leadership and innovative work behavior, and provides practical insights for practitioners to create more inclusive environments that support innovative work behavior.